2021
DOI: 10.1101/2021.08.17.456603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Working memory capacity of crows and monkeys arises from similar neuronal computations

Abstract: Complex cognition relies on flexible working memory, which is severely limited in its capacity. The neuronal computations underlying these capacity limits have been extensively studied in humans and in monkeys, resulting in competing theoretical models. We probed the working memory capacity of crows (Corvus corone) in a change detection task, developed for monkeys (Macaca mulatta), while we performed extracellular recordings of the prefrontal-like area nidopallium caudolaterale. We found that neuronal encoding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…For example, the capacity of WM, the number of individual items that can be maintained simultaneously, is comparable between crows and macaque monkeys (Balakhonov & Rose, 2017). Even single neuron correlates of WM in birds are virtually identical to those in mammals (Ditz & Nieder, 2016, 2020; Moll & Nieder, 2015; Rinnert et al, 2019; Rose & Colombo, 2005) and we recently found that this also extends to the neurophysiological limits of WM capacity (Buschman et al, 2011; Hahn et al, 2021).…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…For example, the capacity of WM, the number of individual items that can be maintained simultaneously, is comparable between crows and macaque monkeys (Balakhonov & Rose, 2017). Even single neuron correlates of WM in birds are virtually identical to those in mammals (Ditz & Nieder, 2016, 2020; Moll & Nieder, 2015; Rinnert et al, 2019; Rose & Colombo, 2005) and we recently found that this also extends to the neurophysiological limits of WM capacity (Buschman et al, 2011; Hahn et al, 2021).…”
Section: Introductionsupporting
confidence: 52%
“…4C) that simultaneously promotes selective neuronal activity without runaway excitation due to divisive normalization (Fries, 2015; Lundqvist et al, 2010). Together with analysis from single-neuron activity in crows (Hahn et al, 2021), it suggests that crow gamma could have a similar role in selection and normalization despite being implemented on a different neural substrate.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…One could question why only the low size clique percolation in the human brain is possible although naively we could expect that the brain would prefer the higher working memory capacity. In particular a limit of the working memory capacity for human is higher then of other animals 35 and it is assumed that higher working memory corresponds to higher intellect. The answer certainly should involve some evolutionary arguments and at least two alternative scenario are possible.…”
Section: Simulation Of Clique Organization In Free Association Networkmentioning
confidence: 99%